Medical chemistry and biochemistry / Introduction to enzymology, membrane biochemistry and biochemistry of genetic information - Račay, Peter; Jesseniova lekárska fakulta UK (Bratislava : Comenius University in Bratislava, 2021)
This text book is about introduction to learning biochemistry within the context of cell biology in preparation for studying clinical medicine. Therefore many examples of pathologic conditions in connection with basic chemistry and biochemistry are included in this text book. In addition, some aspects of biochemistry should be presented in the context of the cell, tissue and body structures. Due to this fact, students using this text book should have some basic knowledge of general and cell biology, cytology and histology. This might overload presented text book, however, according to the author's experience of teaching of biochemistry at medical faculty, students deal better with biochemistry if they are provided with examples showing the connection between the basic knowledge and clinical medicine. In addition, recent human medicine is more and more causal and based on knowledge of the molecular mechanisms of normal and pathologic processes therefore it seems to be essential to show the connections between biomolecules and human disorders.
Bibliogr. odkazy
Keywords: lekárstvo; biochémia; chémia; enzýmy a koenzýmy; membrány; štruktúry genetické; biochémia lekárska; učebnica